2021
DOI: 10.1186/s41938-020-00350-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antibiosis potential of Bacillus sp. against the soil-borne fungal pathogen Sclerotium rolfsii Sacc. (Athelia rolfsii (Curzi) Tu & Kimbrough)

Abstract: Background This study aimed to investigate the rhizosphere bacterial isolates’ antagonistic property against the soil-borne fungal phytopathogen, Sclerotium rolfsii Sacc. (Athelia rolfsii (Curzi) Tu & Kimbrough). The chemical control of the disease caused by S. rolfsii is economically and environmentally unsustainable, and therefore, a bio-control agent in the form of rhizospheric bacteria is gaining importance. Main body Five rhizospheric Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
2
8
0
2
Order By: Relevance
“…These results suggest that the antifungal compounds produced by the bacteria were responsible for the suppression of plant pathogen and the disease. Antibiosis by bacterial antagonists is implicated as a typical mechanism in their biocontrol activity against S. rolfsii [51]. Additionally, other data of this study demonstrated that the tested rhizobacteria inhibited oxalic acid production of S. rolfsii and showed abilities to use oxalic acid as a growth substrate.…”
Section: Discussionsupporting
confidence: 57%
“…These results suggest that the antifungal compounds produced by the bacteria were responsible for the suppression of plant pathogen and the disease. Antibiosis by bacterial antagonists is implicated as a typical mechanism in their biocontrol activity against S. rolfsii [51]. Additionally, other data of this study demonstrated that the tested rhizobacteria inhibited oxalic acid production of S. rolfsii and showed abilities to use oxalic acid as a growth substrate.…”
Section: Discussionsupporting
confidence: 57%
“…Previous reports have also identified siderophore production as a biocontrol mechanism against fungal pathogens in other plant species ( El-Sayed et al, 2014 , Vinayarani and Prakash, 2018 ). Bacillus subtilis , B. siamensis and B. amyloliquefaciens are able to produce siderophores, which may help to decrease Fusarium wilt caused by Fol as reported with other isolates of the B. subtilis group ( Kumari et al, 2021 ). The bacteria in this study did not show any chitin degradation properties.…”
Section: Discussionmentioning
confidence: 79%
“…Bacillus spp. also use some other mechanism like antibiosis and competition to colonize with S. rolfsiis sclerotia and mycelium (Gholami et al, 2014;Kumari et al, 2021). Hence, the disease severity was lower in the bacteria treated chickpea plants as compared to the non-treated plants.…”
Section: Resultsmentioning
confidence: 99%